Type 2 Diabetes Mellitus (Type 2 DM) incidence and associated factors: a cross sectional study in Istanbul, Turkey - Kalkan, Indrani; Kılıçarslan, Menekşe (Progress in Nutrition, 2019)
Background: Incidence of Type 2 Diabetes Mellitus (Type 2 DM) is considerably high in Turkey and has been associated with risk factors as obesity, nutrition, socioeconomic status and education. Lifestyle-intervention programs may be of special significance in impaired glucose tolerance and development of DM. Objective: This research was planned as a observational cross-sectional study, in order to determine the major factors associated with the incidence of DM. Methods: The study was carried out in Beykoz Public Hospital Tepeustu, Istanbul. The patient population comprised of 18970 patients with Type 2 DM. Incidence of diabetes were evaluated according to gender, age, education, income level with descriptive statistical analyses. Results: DM incidence was highest in females of age group 61-75 years (31,29%) followed by men within the same age group (16,35%). Also the incidence was highest in the individuals with primary school education (37,97%) followed by individuals with no formal education (32,43%). DM increased as income decreased with highest percentages (36,56%) recorded among patients having personal income less than 1000 TL per month. Conclusion: As the study indicates poverty and lack of education are major contributing factors; effective policies aimed at decreasing poverty and increasing education level should be implemented in the lower strata of the society.